2016
DOI: 10.1021/acs.biomac.6b00603
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Aggregation under Hydrothermal Pretreatment Conditions

Abstract: Cellulose, the most abundant biopolymer on Earth, represents a resource for sustainable production of biofuels. Thermochemical treatments make lignocellulosic biomaterials more amenable to depolymerization by exposing cellulose microfibrils to enzymatic or chemical attacks. In such treatments, the solvent plays fundamental roles in biomass modification, but the molecular events underlying these changes are still poorly understood. Here, the 3D-RISM-KH molecular theory of solvation has been employed to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 62 publications
0
49
0
2
Order By: Relevance
“…Across this surface, often termed the internal surface, 67 numerous hydrogen bonds join the microfibrils that belong to the same aggregate. 68 Despite earlier suggestions that cellulose surfaces within aggregates are inaccessible to solvents, 40 it has been shown that moisture is able to penetrate between microfibrils to some extent. 45 Hence, we propose here that the mobile WAC consists of inter-aggregate water molecules adsorbed at the external surfaces, while water molecules responsible for the observed immobile WAC phase reside at intra-aggregate microfibril interfaces.…”
Section: The Behavior Of the Immobile Water Componentmentioning
confidence: 96%
See 1 more Smart Citation
“…Across this surface, often termed the internal surface, 67 numerous hydrogen bonds join the microfibrils that belong to the same aggregate. 68 Despite earlier suggestions that cellulose surfaces within aggregates are inaccessible to solvents, 40 it has been shown that moisture is able to penetrate between microfibrils to some extent. 45 Hence, we propose here that the mobile WAC consists of inter-aggregate water molecules adsorbed at the external surfaces, while water molecules responsible for the observed immobile WAC phase reside at intra-aggregate microfibril interfaces.…”
Section: The Behavior Of the Immobile Water Componentmentioning
confidence: 96%
“…Assumedly, the microfibril-microfibril contact within the aggregates is more regular and stronger than the contact between different aggregates. 68,69 If so, swelling of the aggregates and thereby the resulting microfibril-microfibril separation is limited since it proceeds against strong forces between the microfibrils within the aggregate. That limitation must be weaker at the external surfaces.…”
Section: The Behavior Of the Immobile Water Componentmentioning
confidence: 99%
“…10,16 Mathematical modelling has also become a powerful, complementary analytical technique to study the structure and behavior of cellulose in various environments. 16,17 In a recent study, applying transmission electron microscopy on ultrathin wood sections, we observed that EFs form an out-of-plane angle with respect to the longitudinal cell axis. 18 Here, following our previous work, transmission electron tomography and mathematical modelling have been applied to observe nanoscale geometries and assembly of EFs in native cell walls.…”
Section: Introductionmentioning
confidence: 94%
“…It is also found from C4 region in Figure a that the accessibility to cellulose decreases and the inaccessibility increases with the increase of pretreatment severity, which means the average fibril aggregate dimension is increaseing. The enlargement of the fibril and fibril aggregate can be explained by thermally induced recrystallization and aggregate growth, which is probably driven by prevalent cellulose‐cellulose attractive interactions under hydrothermal pretreatment . With the increase of pH in Figure b, the signal of accessible fibril becomes increasing, which indicates high pH does not favor the fibril aggregate growth and will leave more void space (or pores) for facilitating the penetration of cellulase.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of enzymatic hydrolysis of cellulose could be greatly increased after thermal and/or chemical pretreatment. A lot of work has been done on the effect of the pretreatment on the alterations of ultrastructural cellulose and the impact of these ultrastructural modifications of cellulose on the efficiency of enzymatic hydrolysis …”
Section: Introductionmentioning
confidence: 99%